2007
DOI: 10.1002/chem.200700097
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Basicities of Diamines in the Gas Phase, Acetonitrile, and Tetrahydrofuran

Abstract: A comprehensive basicity study of alpha,omega-alkanediamines and related bases has been carried out. Basicities in acetonitrile (AN, pK(a) values), tetrahydrofuran (THF, pK(alpha) values), and gas phase (GP, GB values), were measured for 16, 14, and 9 diamine bases and for several related monoamines. In addition the gas-phase basicities and equilibrium geometries were computed for 19 diamino bases and several related monoamines at the DFT B3LYP 6-311+G** level. The effects of the different factors (intrinsic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…Intramolecular hydrogen bonding has been also found to play an important role in the conformational preferences of monocharged a,x-alkanediamines [10,12,13]. The H-bond parameters and energies are identical in the a,xalkanediamines and CHDAs except when the amino groups occupy the 1,4-positions.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Intramolecular hydrogen bonding has been also found to play an important role in the conformational preferences of monocharged a,x-alkanediamines [10,12,13]. The H-bond parameters and energies are identical in the a,xalkanediamines and CHDAs except when the amino groups occupy the 1,4-positions.…”
Section: Resultsmentioning
confidence: 94%
“…Regarding charged diamines, some works have been performed in a,x-alkanediamines [10][11][12][13][14][15], but none in cyclic aliphatic diamines.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the unusually high basicity of proton sponges is significantly influenced by the formation of intramolecular hydrogen bonds [13]. The tendency of diamines and diols to form IMHBs has been recognized for quite some time [14][15][16][17][18], but only recently, several papers of Raczynska et al [19][20][21][22][23], Koppel and coworkers [24] and theoretical investigations of Maksić and coworkers [25][26][27] have shown that the existence of flexible intramolecular hydrogen bonds plays a significant role in the tailoring of organic superbases. A representative example is provided by a guanidine bearing three 3-(N,N-dimethylamino)propyl groups, for which a gas-phase basicity comparable to those of phosphazenes has been predicted [28].…”
Section: Introductionmentioning
confidence: 99%
“…A second-order rate constant of 0.20±0.01/(s M) was calculated. TBD (pK a in acetonitrile=26.03) [32] is a stronger basic organocatalyst than piperazine (pK a in acetonitrile=18.69) [33]. Consequently, when the same reaction was carried out at 65°C and under ambient pressure conditions as reported for the TBD wall-coated glass microreactor [15], the reaction proceeded about ten times slower with a second-order rate constant of 1.18±0.01× 10 −2 /(s M) against 0.10±0.01/(s M), reported in the literature for the TBD-catalyzed reaction [15].…”
Section: Resultsmentioning
confidence: 99%